2017
DOI: 10.1103/physrevc.96.014319
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of Tc100 β decay with total absorption γ -ray spectroscopy

Abstract: The β decay of 100 Tc has been studied by using the total absorption γ -ray spectroscopy technique at the Ion Guide Isotope Separator On-Line facility in Jyväskylä. In this work the new Decay Total Absorption γ -ray Spectrometer in coincidence with a cylindrical plastic β detector has been employed. The β intensity to the ground state obtained from the analysis is in good agreement with previous high-resolution measurements. However, differences in the feeding to the first-excited state as well as weak feeding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 81 publications
1
10
0
Order By: Relevance
“…The Decay Total Absorption γ-ray Spectrometer (DTAS) [351] has been successfully commissioned at IGISOL and has already provided e.g. β-decay intensities of importance for the r-process nuclear reaction network calculations [352] and could in principle be used for the β-Oslo method. The Selective Production of Exotic Species (SPES) facility is the upgrade path envisioned for LNL [354].…”
Section: Jyväskylä Accelerator Laboratorymentioning
confidence: 99%
“…The Decay Total Absorption γ-ray Spectrometer (DTAS) [351] has been successfully commissioned at IGISOL and has already provided e.g. β-decay intensities of importance for the r-process nuclear reaction network calculations [352] and could in principle be used for the β-Oslo method. The Selective Production of Exotic Species (SPES) facility is the upgrade path envisioned for LNL [354].…”
Section: Jyväskylä Accelerator Laboratorymentioning
confidence: 99%
“…3. The summing-pileup distortion, present in all our measurements, was calculated as in previous works [16,18,19,47] with a Monte Carlo (MC) procedure based on the random superposition of two stored events within the ADC gate [46,48].…”
Section: Methodsmentioning
confidence: 99%
“…We also investigated nuclides below 68 Ni (Z = 28, N = 40), namely 69,70 Co and 67 Fe. 68 Ni has some doubly magic features, such as high excitation energy of the first 2 + state and low transition strength B(E2; 0 g.s. → 2 + 1 ) [23,24].…”
Section: Nuclei In the Vicinity Of 78 Nimentioning
confidence: 99%
“…The mass measurements of 69 Co and 67 Fe are also important for accurate neutron separation energies needed to calculate neutron-capture and their inverse photodisintegration rates in the astrophysical rapid neutron capture process (r process) [34,35]. Sensitivity studies [36] have shown that 67 Fe(n, γ ) 68 Fe and 68 Co(n, γ ) 69 Co have a strong impact on the calculated r-process abundances. With the new JYFLTRAP measurements, we could reduce the mass-related uncertainties in these impactful neutron-capture rates.…”
Section: Nuclei In the Vicinity Of 78 Nimentioning
confidence: 99%
See 1 more Smart Citation